2012
DOI: 10.2147/rmhp.s30707
|View full text |Cite
|
Sign up to set email alerts
|

Health risk reduction behaviors model for scavengers exposed to solid waste in municipal dump sites in Nakhon Ratchasima Province, Thailand

Abstract: The aim of this study was to evaluate the effect of comprehensive health risk protection behaviors, knowledge, attitudes, and practices among scavengers in open dump sites. A control group of 44 scavengers and an intervention group of 44 scavengers participated in this study. Interventions included the use of personal protective equipment, health protection training, and other measures. The analysis showed significant differences before and after the intervention program and also between the control and interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
39
2
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 5 publications
12
39
2
9
Order By: Relevance
“…Further investigation will be required to understand the geographic variation of waste picking as a primary source of household incomes among regions and countries. The landfill is a hazardous place to work (Oyelola et al, 2001;Thirarattanasunthon et al, 2012), but it is also an economic opportunity for many, while also providing certain societal benefits. Recycling MSW can support sustainable communities and is a well-established business in developed (high income) countries (Sicular, 1992;Beukering and Bouman, 2001).…”
Section: Eradicate Extreme Poverty and Hunger: Mdgmentioning
confidence: 99%
See 3 more Smart Citations
“…Further investigation will be required to understand the geographic variation of waste picking as a primary source of household incomes among regions and countries. The landfill is a hazardous place to work (Oyelola et al, 2001;Thirarattanasunthon et al, 2012), but it is also an economic opportunity for many, while also providing certain societal benefits. Recycling MSW can support sustainable communities and is a well-established business in developed (high income) countries (Sicular, 1992;Beukering and Bouman, 2001).…”
Section: Eradicate Extreme Poverty and Hunger: Mdgmentioning
confidence: 99%
“…Waste pickers do not necessarily live in the poorest slums, but they are still considered to be a vulnerable population in terms of poverty (Torun et al, 2006). Landfill slum residents are reported to lack education, access to improved sources of drinking water, and sanitation facilities (Oyelola et al, 2001;Rankokwane and Gwebu, 2006;Thirarattanasunthon et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Agunwamba et al, 1998;Longe et al, 2009;Nabegu, 2012). According to Thirarattanasunthon et al (2012); Butu and Mshelia (2014), studies have also shown that uncollected waste have contributed to flooding, breeding of insects and rodents vectors which spread diseases such as cholera, typhoid fever, lassa fever, diarrhoea, dysentery, schistosomiasis, etc. (Asbor and Edjere, 2016).…”
Section: Introductionmentioning
confidence: 99%